Sensory Evaluation of Gluten-Free Wet Noodles Made from Potato (Solanum tuberosum L.) Flour with the Addition of Kersen (Muntingia calabura L.) Leaves Powder - Kusumasari, Findi Citra; Handayani, Anna Mardiana; Setyowati, Lisus; Satya, Malinda Capri Nurul (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2023)
Gluten-free noodles are a processed food that has become an alternative food for gluten-intolerant patients. This study investigated the effect of gluten-free wet noodles made from potato flour and tapioca starch (T1 = 40:60%, T2 = 50:50% and T3 = 60:40%) and its addition of kersen leaves powder (K1 = 5%, K2 = 10% and K3 = 15%) on consumer acceptability using hedonic and descriptive tests with color, aroma, taste and texture attributes involved 25 semi-trained panelists. The results showed that there was a significant difference (p < 0.05) in the level of consumer preference for color and texture and no significant difference (p > 0.05) in aroma and taste. The preferred formulations in terms of color were T1K3, which contained 40% potato flour and 60% tapioca starch with 15% kersen leaves powder, and T2K3, which included 50% potato flour and 50% tapioca starch with 15% kersen leaves powder. T2K3 was also preferred for aroma attributes, while T1K1, for taste attributes, contained 40% potato flour and 60% tapioca starch with 5% kersen leaves powder. T1K2 was preferred for texture attributes, which included 40% potato flour and 60% tapioca starch with 10% kersen leaves powder. Hedonic descriptive testing results showed significant differences for all formulations for each attribute. The current study’s findings indicated that the T1K2 formulation consisting of 40% potato flour and about 60% tapioca starch with 10% kersen leaves powder got the highest score on hedonic tests based on the results from all attributes.